Bimetallic FeCo−N−C Catalyst for Efficient Oxygen Reduction Reaction. Issue 10 (22nd April 2022) - Zhou, Meng; Zhu, Zhijun; Ju, Yuan; Zhai, Yanling; Jiao, Lei; Liu, Minmin; Yang, Wenxiu; Tang, Jianguo
Abstract: Oxygen reduction reaction (ORR) is being deeply studied because of its significance in energy storage and conversion. It is an urgent and challenging task to explore low‐cost ORR catalysts with excellent activity and outstanding long‐term stability. Herein, we report an efficient bimetallic FeCo catalyst based on nitrogen‐doped carbon (FeCo−NC) for ORR by pyrolysis of FeCo‐1, 10‐phenanthroline complexes (FeCo‐phen) supported on ZIF‐8. The as‐synthesized FeCo−NC catalyst shows excellent ORR activity, improved durability and excellent methanol cross poisoning resistance, which are ascribed to the formation of metal‐N−C active sites, the synergistic effect between Fe and Co, as well as the porous structure. Abstract :